The Performance and Trajectory of Medical Students With Disabilities: Results From a Multisite, Multicohort Study. (18th February 2022) - Meeks, Lisa M.; Plegue, Melissa; Swenor, Bonnielin K.; Moreland, Christopher J.; Jain, Sharad; Grabowski, Christina J.; Westervelt, Marjorie; Case, Ben; Eidtson, William H.; Patwari, Rahul; Angoff, Nancy R.; LeConche, Jack; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Purpose: To conduct a post–Americans with Disabilities Act Amendments Act of 2008 multisite, multicohort study called the Pathways Project to assess the performance and trajectory of medical students with disabilities (SWDs). Method: From June to December 2020, the authors conducted a matched cohort study of SWDs and nondisabled controls from 2 graduating cohorts (2018 and 2019) across 11 U.S. MD-granting medical schools. Each SWD was matched with 2 controls, one from their institution and, whenever possible, one from their cohort for Medical College Admission Test score and self-reported gender. Outcome measures included final attempt Step 1 and Step 2 Clinical Knowledge scores, time to graduation, leave of absence, matching on first attempt, and matching to primary care. Results: A total of 171 SWDs and 341 controls were included; the majority of SWDs had cognitive/learning disabilities (118/171, 69.0%). Compared with controls, SWDs with physical/sensory disabilities had similar times to graduation (88.6%, 95% confidence interval [CI]: 77.0, 100.0 vs 95.1%, 95% CI: 90.3, 99.8; P = .20), Step 1 scores (229.6 vs 233.4; P = .118), and match on first attempt (93.9%, 95% CI: 86.9, 100.0 vs 94.6%, 95% CI: 91.8, 97.4; P = .842), while SWDs with cognitive/learning disabilities had lower Step 1 scores (219.4; P < .001) and were less likely to graduate on time (81.2%, 95% CI: 69.2, 93.2; P = .003) and match on first attempt (85.3%, 95% CI: 78.0, 92.7; P = .009). Accommodated SWDs had Step 1 scores that were 5.9 points higher than nonaccommodated SWDs (95% CI: –0.7, 12.5; P = .08). Conclusions: Structural barriers remain for SWDs with cognitive/learning disabilities, which could be partially mitigated by accommodations on high-stakes exams.